The Semantic Basis for Selectional Restrictions - Melchin, Paul (Université d'Ottawa / University of Ottawa, 2019)
In this thesis I investigate the relationship between the semantics of a verb and its selectional restrictions, which determine how many and what kind of arguments it must occur with in a clause. For most verbs, these restrictions are predictable from the semantics of the verb, but there are pairs of verbs with very similar semantics that differ in their argument restrictions. For example, both ask and wonder can take questions as their complements (John asked/wondered what time it was), but of the two, only ask can take a noun phrase complement with a question-like interpretation (John asked/*wondered the time). Similarly, while both eat and devour are verbs of consumption, the object can be omitted with eat but not devour (John ate/*devoured yesterday). Due to these and similar examples, many linguists have claimed that selectional restrictions are to some extent arbitrary and unpredictable from the semantics, and therefore must be learned as part of our knowledge of the relevant verbs. In this thesis I argue that these differences are not arbitrary; they recur across languages, and they can be predicted on the basis of lexical semantics, meaning they do not need to be learned on a word-by-word basis. In order for selectional features to be eliminated from the grammar, and replaced with semantic generalizations, two things must be shown. First, it must be demonstrated that the elements being selected for can be defined in terms of their semantics, rather than their syntactic properties. If not, the selectional properties could not be considered to be fully predictable based on the semantics of the selecting and selected items. Second, it must be shown that the selectional restrictions of a predicate are predictable from components of the selecting predicate’s meaning. In other words, the semantics of both the selected and the selecting elements must be accounted for. I focus mainly on the semantics of selected elements in Chapter 2, and on selecting elements in Chapters 3 and 4. Chapter 2 provides a brief review of the literature on selectional features, and argues that the elements being selected need not be defined in terms of their syntactic category and features. Instead, what are selected for are the semantic properties of the selected items. While the relationship between syntactic and semantic categories and properties is often systematic, it is not always, which can make it difficult in certain cases to determine the semantic basis for predicting what elements will be selected. Specifically, I argue that what appears to be selection for clausal categories (CPs or TPs) is in fact selection for propositional entities (including questions, assertions, facts, and so on); apparent selection for bare verb phrases (vPs) is selection for eventualities (events or states); and apparent selection for nominals (DPs) is selection for objects or things. Only properties of the nearest semantic entity (i.e., excluding elements embedded therein) can be selected for. In this way, I account for the selectional asymmetries between clausal and nominal complements noted by Bruening (2009) and Bruening et al. (2018): predicates selecting clausal complements can only select for (semantic) properties of the upper portion of the clause (in the CP domain), not for the lower portion (the vP domain), while predicates taking nominal complements can select for any properties of the nominal rather than being restricted to the upper portion. Since all syntactic properties of items are encoded as features, on a syntactic account it is expected that all features should be involved in selectional restrictions, contrary to fact; the semantic approach taken here allows for a principled explanation of what can and cannot be selected for. In Chapters 3 and 4 I turn to the lexical semantics of selecting elements, showing that these too are involved in determining selectional restrictions. I start in Chapter 3 by looking at c-selection (i.e., syntactic selection), specifically the case of eat versus devour. As mentioned above, their selectional properties of these two verbs differ in that the complement of eat is optional, while that of devour is obligatory, despite the two verbs having similar meanings. I show that this is due to the aspectual properties of these verbs: devour denotes an event where the complement necessarily undergoes a complete scalar change (i.e., it must be fully devoured by the end of the event), which means that the complement must be syntactically realized (Rappaport Hovav and Levin 2001; Rappaport Hovav 2008). Eat, on the other hand, does not entail a complete change of state in its complement, and so the complement is optional. I show that the correlation between scalar change entailments and obligatory argument realization holds for a wider group of verbs as well. Thus, the c-selectional properties of eat, devour, and similar verbs need not be stipulated in their lexical entries. In Chapter 4 I turn to the selection of complements headed by a particular lexical item, as with rely, which requires a PP complement headed by on, a phenomenon commonly referred to as l-selection. I show that the sets of verbs and prepositions involved in l-selection, and the observed verb-preposition combinations, are not fully random but can instead be (partially) predicted based on the thematic properties of the items in question. Furthermore, I show that there are different kinds of l-selecting predicates, and one kind is systematically present in satellite-framed languages (like English) and absent in verb-framed languages (like French), based on the Framing Typology of Talmy (1985, 1991, 2000). I account for this difference by analyzing l-selection as an instance of complex predicate formation, and showing that a certain kind of complex predicate (exemplified by rely on) is possible in satellite-framed languages but not in verb-framed languages. Thus, I show that the features that get selected for are semantic features, and that the problematic cases of eat versus devour and l-selection have semantic correlates, and need not be stipulated in the lexicon. While this leaves many instances of selectional features unaccounted for, it provides proposals for some components of lexical semantics that are relevant to selection, and demonstrates that a research program directed toward eliminating the remaining cases is plausibly viable.
Keywords: Syntax; Semantics; Selection; Argument structure